Measuring Economic Preferences with Surveys and Behavioral Experiments - Michael Kosfeld; Zahra Sharafi; Maíra Sontag González; Na Zou (CESifo GmbH, 2025)
Developing reliable and practicable measures of economic preferences is a crucial task for empirical economic research with high value for both theory and applications. Here, we present results from a first comprehensive "behavioral validation analysis" of the Global Preference Survey Module (GPS) and the corresponding Preference Survey Module (PSM) developed by Falk et al. (2018, 2023) that have been widely used for the measurement and analysis of economic preferences on a global scale. Our key questions are how well GPS and PSM modules explain behavior in incentivized choice experiments in other countries than in the original validation in Germany, and to what extent survey items and modules developed from behavioral experiments in different countries and cultures resemble one another. Our current results, which are based on experiments in three very diverse countries—China, Iran, and Kenya—show that many GPS and PSM survey items predict behavior in incentivized choice experiments, but coefficients vary and are not always sizable. Quantitative items, which are based on hypothetical choice experiments, are consistently selected into survey modules, whereas the best qualitative items differ between countries. At the same time, the contribution in terms of explanatory power of these latter items is comparably lower. Our analysis provides a first empirical basis for the development of survey modules that reliably predict behavior in incentivized choice experiments and real-life situations across diverse countries and contexts. Additional results, including principal component analysis and prediction of real-life behavior, highlight important gaps that warrant further investigation in future research.
Keywords: C83; C91; D01; 330; economic preference; measurement; survey; experiment